Pelatihan Eduwisata di Balai Riset dan Inovasi Daerah (BRIDA) bagi Mahasiswa Universitas di Kota Mataram dalam Pengembangan Kompetensi Pemandu Wisata Edukasi - Menik Aryani; Lu'luin Najwa (Jurnal Dedikasi Madani, 2026)
This community service program aims to improve the competence of university students in Mataram City as educational tour guides for early childhood education, particularly students at the kindergarten (TK) and elementary school (SD) levels. The program was conducted at the Balai Riset dan Inovasi Daerah (BRIDA) of West Nusa Tenggara Province, which serves as a strategic venue for science-based educational tourism. The background of this activity stems from the lack of trained human resources in the edutourism sector who understand the characteristics and developmental needs of young children. The training program was designed using a competency-based training (CBT) approach covering three main domains: child development knowledge, interactive science communication skills, and practical guiding techniques. Activities included workshops, role-playing simulations, field practice, and reflective evaluations. Participants consisted of 35 university students from various study programs in Mataram. The results showed significant improvement in participants' understanding of child learning characteristics, their ability to design age-appropriate learning activities, and their confidence in conducting interactive tours. Teachers and parents accompanying the children also expressed high satisfaction with the tour guide performance demonstrated during simulation sessions. This program demonstrates that structured edutourism training at innovation centers can effectively build the capacity of prospective tour guides who are responsive to the developmental needs of young learners, and is recommended for wider adoption by other local research and innovation agencies.